GAMBARAN KENAIKAN BERAT BADAN IBU AKSEPTOR KB SUNTIK 3 BULAN DI PUSKESMAS PEMBANTU KEBONSARI KABUPATEN JEMBER - Nanik Fitriyah (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2015)
One of the side effects of the three-monthly injective contraceptive device is the increase on the acceptor’s body weight. The DMPA injective contraceptive device may stimulate the control center of hypothalamus appetite that causes a person to eat more than usual portion which allows her to gain weight. The constant increase will cause overweight or obesity which, in turn, causing several chronic diseases like Diabetes Mellitus, hypertension, stroke and cardiac attack. This research is designed as a descriptive-quantitative one. Results ofthe research reveal that the average increase of body weight is 4,5 kilograms;while the value of the median of body weight increase is 55 kilograms; and the modus of the body weight increase is 5 kilograms. The conclusion of this research states that body weight increase is stimulated by a raise on progesterone hormone incurred in the three-monthly injective contraceptive device, altough there are several other factors to contribute to one’s body weight increase like physical activities and food intake, respectively.